Hubungan Tingkat Pengetahuan dan Sikap dengan Perilaku Mengatasi Ketidaknyamanan pada Masa Klimakterium - Purbowati, Niken; Hajrah, Wa ode; Nuraini, Novia (Poltekkes Kemenkes Palu, 2019)
Climacteric is a transitional period from the reproductive phase to the old age phase (senium). Climacteric period 40-85% of women have complaints both physically and psychologically. The differences in knowledge based on personal backgrounds cause the attitude of each individual is different in overcoming the inconvenience of the climacteric phase. This study aims to determine the relationship between the level of knowledge and attitudes towards overcoming discomfort during the climacteric phase. It was a descriptive-analytic research method using a cross-sectional research design. The research sample was 81 respondents. Sampling was stratified random sampling, that is, samples taken per work area randomly. Statistical tests use logistic regression. The results of 81 mothers showed that the proportion of mothers with good knowledge was 87.9%, compared to a lack of knowledge as many as 20.8%. There was a significant relationship between knowledge and behavior to overcome climacteric discomfort (p = 0.029; CI95% = 1.2-27.1). Mothers with good knowledge had a 5.7 times higher chance to behave well in dealing with discomfort during climacteric times, compared to mothers with less knowledge after being controlled by attitude, family roles, and health worker roles.